Minding the gap—Providing quality transplant care for South African children with acute liver failure. (1st September 2020) - Bruckmann, Eduard K.; Beretta, Marisa; Demopolous, Despina; Brannigan, Lliam; Bouter, Carolyn; Maher, Heather; Etheredge, Harriet R.; Fabian, June; Haeri Mazanderani, Ahmad; Britz, Russel; Loveland, Jerome; Botha, Jean F.
Abstract: Pediatric ALF is rare but life‐threatening and may require urgent transplantation. In low and middle‐income countries, access to transplantation is limited, deceased organ donation rates are low, and data on outcomes scarce. The Wits Donald Gordon Medical Centre, in Johannesburg, is one of only two centers in South Africa that perform pediatric liver transplant. We describe the etiology, clinical presentation, and outcomes of children undergoing liver transplant for ALF at our center over the past 14 years. We performed a retrospective chart review of all children undergoing liver transplantation for ALF from November 2005 to September 2019. Recipient data included demographics, clinical and biochemical characteristics pretransplant, post‐operative complications, and survival. We conducted descriptive data analysis and used the Kaplan‐Meier method for survival analysis. We performed 182 primary pediatric liver transplants. Of these, 27 (15%) were for ALF, mostly from acute hepatitis A infection (11/27;41%). Just over half of the grafts were from living donors (15/27;56%), and five grafts (5/27;19%) were ABO‐incompatible. The most frequent post‐transplant complications were biliary leaks (9/27;33%). There were two cases of hepatic artery thrombosis (2/27;7%), one of whom required re‐transplantation. Unadjusted patient and graft survival at one and 3 years were the same, at 81% (95% CI 61%‐92%) and 78% (95% CI 57%‐89%), respectively. At WDGMC, our outcomes for children who undergo liver transplantation for ALF are excellent. We found workable solutions that effectively addressed our pervasive organ shortages without compromising patient outcomes.